2021
DOI: 10.1111/gwao.12727
|View full text |Cite
|
Sign up to set email alerts
|

Emotional and financial health during COVID‐19: The role of housework, employment and childcare in Australia and the United States

Abstract: During the first few months of the COVID‐19 pandemic, the world witnessed major economic, school, and daycare closures. We sampled respondents in Australia and the US during the height of the first restrictions to understand how the first quarantine structured their emotional strain and financial worry (825 Australians and 835 Americans aged between 18 and 65; May 2–3, 2020; source YouGov). We apply structural equation modeling to demonstrate that the emotional well‐being impacts of COVID‐19 are not only gende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 46 publications
2
17
0
Order By: Relevance
“…The present findings also coincide with research on the ongoing COVID-19 pandemic which have, to date, overwhelmingly shown how stress about COVID-19 itself and about the lockdowns and long-term impact of the pandemic have been detrimental to our well-being (Allen et al, 2021;Avsec et al, 2021;Cheng et al, 2021;Ruppanner et al, 2021;Salomon et al, 2021;Wang et al, 2021). Evidence for significant moderated mediation in the furry sample provides preliminary evidence for the fact that those who are under more stress may rely increasingly on their social support networks as a means of coping and resilience.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The present findings also coincide with research on the ongoing COVID-19 pandemic which have, to date, overwhelmingly shown how stress about COVID-19 itself and about the lockdowns and long-term impact of the pandemic have been detrimental to our well-being (Allen et al, 2021;Avsec et al, 2021;Cheng et al, 2021;Ruppanner et al, 2021;Salomon et al, 2021;Wang et al, 2021). Evidence for significant moderated mediation in the furry sample provides preliminary evidence for the fact that those who are under more stress may rely increasingly on their social support networks as a means of coping and resilience.…”
Section: Discussionsupporting
confidence: 89%
“…Well-being detriments are not limited to those fighting the pandemic on the front lines either. The general population has been shown to experience a wide range of symptoms associated with the fear of the pandemic, with the lockdown, and with the uncertainty associated with these changes (e.g., Ruppanner et al, 2021), including anxiety (Cheng et al, 2021), disordered eating (Wang et al, 2021), loneliness and depression (Allen et al, 2021), decreased satisfaction of basic needs (Avsec et al, 2021), and even reductions in brain volume (Salomon et al, 2021). Aversive outcomes have been noted in the young (Varma et al, 2021) as well as in the elderly (Sirin et al, 2021), in parents and in children (Martiny et al, 2021), in undergraduate students (Zinchenko et al, 2021), and in people with disabilities (Sakiz, 2021).…”
Section: Covid-19 As a Threat To Well-beingmentioning
confidence: 99%
“…A rising body of research documents the gendered impact of the COVID‐19 pandemic on workers in Western countries, including the US (Bahn et al., 2020 ; Collins et al., 2021 ), Canada (Qian & Fuller, 2020 ), the UK (Chung et al., 2021 ), and Australia (Craig & Churchill, 2021 ; Ruppanner et al., 2021 ). Findings from these studies show that layoffs, exposure to the virus, and the challenge of combining working from home, childcare, home‐schooling, and domestic labor have disproportionately affected women (Bahn et al., 2020 ; Chung et al., 2021 ; Qian & Fuller, 2020 ; Ruppanner et al., 2021 ). The impact of COVID‐19 on mothers who work outside the home is significant, with implications that are not yet entirely clear (Auðardóttir & Rúdólfsdóttir, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…While men spent more time on unpaid childcare during the pandemic than previously, women retained a disproportionate responsibility for the more mundane and burdensome caring and household duties (Craig and Churchill, 2021). This frustrated women's connection to the workforce during the pandemic, it took a toll on their mental health and well-being (Risse and Jackson, 2021; Ruppanner et al, 2021), and reduced their capacity to engage in sustained knowledge work and thinking time while working from home (Peetz et al, 2022). The likely continuation of remote working post-pandemic spurred further debate in 2021, highlighting the opportunities and risks for women and work into the future (eg Gross and Mostyn, 2021).…”
Section: Gendered Impact Of Covid-19 On Employment and Labour Force P...mentioning
confidence: 99%